2009
DOI: 10.4166/kjg.2009.54.6.390
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Assessment of Percutaneous Transhepatic Transpapillary Stent Insertion in Malignant Obstructive Jaundice: Regarding the Risk of Pancreatitis and the Effect of Preliminary Endoscopic Sphincterotomy

Abstract: Metallic stent insertion through the intact sphincter of Oddi might have a risk of developing pancreatitis. Further study is needed to elucidate the mechanism of pancreatitis and the way of prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In our study, the incidence of PEP was 4.0% in hilar cholangiocarcinoma and 2.3% in distal cholangiocarcinoma. Although the outcomes with ES for malignant biliary strictures, especially cholangiocarcinoma, are controversial, several previous studies have demonstrated a lower incidence of PEP in the ES group compared to the non-ES group[8,9,31]. Jeong et al[8] investigated the risk of pancreatitis in patients with malignant obstructive jaundice following percutaneous or transpapillary stent placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the incidence of PEP was 4.0% in hilar cholangiocarcinoma and 2.3% in distal cholangiocarcinoma. Although the outcomes with ES for malignant biliary strictures, especially cholangiocarcinoma, are controversial, several previous studies have demonstrated a lower incidence of PEP in the ES group compared to the non-ES group[8,9,31]. Jeong et al[8] investigated the risk of pancreatitis in patients with malignant obstructive jaundice following percutaneous or transpapillary stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…They are, however, reported to be associated with a higher incidence of pancreatitis[6,7]. Previous studies indicate that performing endoscopic sphincterotomy (ES) before stent insertion may lower the incidence of post-ERCP pancreatitis (PEP)[8-10]. ES may also facilitate cannulation of the bile duct during difficult ERCPs, reduce resistance to the passage of stents, improve immediate stent deployment, and increase the luminal diameter of the distal common bile duct (CBD)[9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Results of reports of pancreatitis and stent migration following placement of a metal stent are shown in Table . Jeong et al .…”
Section: Placement Of a Metal Stentmentioning
confidence: 99%
“…Jeong et al . retrospectively studied 90 patients that underwent percutaneous placement or transpapillary placement . They noted pancreatitis in many of the patients that underwent percutaneous placement (odds ratio: 1.87, 95% CI: 0.516–6.761) and in a few of the patients that underwent EST and transpapillary placement (odds ratio: 0.91, 95% CI: 0.656–1.273), but the differences were not statistically significant.…”
Section: Placement Of a Metal Stentmentioning
confidence: 99%
See 1 more Smart Citation